REORIENTASI KEPEMIMPINAN KIAI DI PONDOK PESANTREN SALAFIYYAH : STUDI KEPEMIMPINAN DI PONDOK PESANTREN ASY-SYAFI’IYYAH - Zaini Hafidh; Yayah Rahyasih; An an Aminah; M. Irvan Gunawan (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
This research starts from the thought of kiai leadership that develops salafiyah boarding school environment that tends to form an authoritarian leadership. So the pattern of leadership that occurs in Asy-Syafi'iyyah boarding school whether it has similarities with other boarding schools or has differences. The purpose of this study was to determine the leadership of kiai in Asy-Syafi'iyyah boarding school, authority, decision-making, succession system and regeneration. This research uses qualitative research with a Case Study approach. Data collection techniques are carried out by interviews, observations, and document studies. Data analysis in the form of data unitization, categorization, and interpretation of data and a test data. The results of the study concluded that the pattern of kiai leadership in Asy-Shafi'iyyah boarding school, kiai led by using the leadership style of developers and missionaries, then the type of Democratic and charismatic leadership. The authority of kiai in pesantren is not absolute, he shares Authority and authority with other pesantren elites. Decision making he did use participatory decision making from all elements of pesantren and society. The system of succession and regeneration is carried out scientifically and with a long process, kiai prepares their children to become successors and prepares scientific, experiential and moral competencies for their future successors. This leadership pattern is a mirror of the implementation of KH leadership. Ahmad Syafei at Asy Syafi'iyyah boarding school.